2018
DOI: 10.1097/iae.0000000000001674
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Refractory Macular Edema After Branch Retinal Vein Occlusion Following Intravitreal Bevacizumab

Abstract: If BRVO-ME patients exhibit the above-mentioned characteristics, they may have refractory ME, which should inform treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
3
26
1
Order By: Relevance
“…Alternative or additional pathways may contribute to visual outcomes. Previous studies regarding visual outcomes have focused on the outer layers of the retina, such as the ELM, EZ, and IZ [15][16][17][18]20]. In contrast, there were no significant differences between the recurrence of macular edema and the incidences of ELM or EZ disruption in the current study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Alternative or additional pathways may contribute to visual outcomes. Previous studies regarding visual outcomes have focused on the outer layers of the retina, such as the ELM, EZ, and IZ [15][16][17][18]20]. In contrast, there were no significant differences between the recurrence of macular edema and the incidences of ELM or EZ disruption in the current study.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast, sectional images of the retina can easily be obtained using OCT. In this regard, previous reports have focused on findings from the external limiting membrane (ELM), ellipsoid zone (EZ), and interdigitation zone (IZ) as predictors of visual outcome after macular edema due to BRVO [15][16][17][18]. However, the predictive factors for recurrences have remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, a short distance of occlusion from the disc margin was found to be associated with increased retinal hemorrhage and development of refractory macular edema. [ 31 32 ] Although it was expected that there would be more congestion and ischemic areas in occlusions located close to the vascular root, the FAZ area and visual acuity were not associated with the optic disc-affected AV crossing distance. However, the vessel density was greater in the superficial and deep plexuses of the unaffected macular hemifield when the optic disc-affected AV crossing distance was smaller.…”
Section: Discussionmentioning
confidence: 99%
“…These events increase vascular endothelial growth factor (VEGF) secretion and increase vascular permeability and thus cause macular edema (2,3). Macular edema is the most common cause of visual loss in BRVO (4,5). Laser photocoagulation, intravitreal steroid injection and intravitreal anti-VEGF injection are used for the treatment of macular edema (6,7).…”
Section: Introductionmentioning
confidence: 99%